Technological aspects of pavement improvement of bridges and high aquaplaning areas - ATYNIAN, Armen; DZHALALOV, Makhmudzhan; BRATISKO, Svitlana; TKACHENKO, Roman; SAVCHENKO, Oleksandr (Ways to Improve Construction Efficiency, 2025)
The sharp increase in traffic intensity, the constant increase in weight loads on road surfaces, the use of outdated technologies and low-quality construction materials lead to an accelerated deterioration in the operational characteristics of motorways. This results in typical defects such as rutting, potholes, cracks, deformations and aquaplaning, which directly affect road safety. These processes are particularly critical on artificial structures such as bridges and overpasses, where water drainage is limited and geometric conditions are complex. Weather conditions, in particular heavy summer rains and seasonal snowmelt, are an important factor in the increased risk of accidents in areas with inadequate drainage. Areas with an increased likelihood of aquaplaning require special attention, where traditional design and construction methods are ineffective or technically impossible to implement. In such conditions, promising solutions include the use of the latest road construction materials and structures, in particular porous asphalt concrete and geosynthetic materials with drainage properties. They effectively reduce the depth of the water film, increase the coefficient of wheel adhesion to the road and extend the service life of the pavement. The study found that in order to effectively reduce the risk of aquaplaning, it is necessary not only to comprehensively change the geometric parameters of the road surface (increasing slopes, organising longitudinal and transverse drainage systems, installing wells and gutters), but also to introduce innovative types of road surfaces with improved drainage properties. In areas where geometric reconstruction of the road is limited or technically impossible, for example, within urban areas, on bridges or in tunnels, the use of materials with high water permeability and the ability to quickly remove moisture from the surface becomes particularly relevant. During the study, an analysis was carried out of the relationship between pavement roughness, water layer depth and the coefficient of friction. Experimental measurements of wheel adhesion to the surface were performed under various weather conditions, speeds and loads. Traffic scenarios were also modelled for different longitudinal slope angles, pavement types and braking modes. In addition, the results showed that although the initial investment in the use of the latest materials is slightly higher compared to traditional technologies, the total costs of maintenance, repair and elimination of the consequences of road accidents are significantly reduced. The payback of innovative solutions is already observed in the medium term, which confirms the feasibility of their implementation.